2013
DOI: 10.4172/2157-7439.1000161
|View full text |Cite
|
Sign up to set email alerts
|

Plant In vitro Culture goes Nano: Nanosilver-Mediated Decontamination of Ex vitro Explants

Abstract: Plant tissue culture is a basic and fundamental component of plant biotechnology, and progress in different fields of biotechnology greatly depends on the improvement of this technique. Nowadays, nanomaterials especially Nanosilver [NS], are regularly being used as an antimicrobial agent in medical and environmental fields. In order to assay the efficiency of NS in sterilizing plant seeds and fragile tissues, such as leaf and cotyledon, two important model plants, Arabidopsis and tomato, as well as potato as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 26 publications
0
24
0
2
Order By: Relevance
“…), Arabidopsis (Arabidopsis thaliana), cucurbits, and others. It is suggested that proper use of low-dose Agnanoparticles may even stimulate growth and survival of seedlings or plant juvenile phases, exhibiting concurrently a sterilizing effect against pathogenic microorganisms from their environment to protect plants against diseases in their early stages of life [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…), Arabidopsis (Arabidopsis thaliana), cucurbits, and others. It is suggested that proper use of low-dose Agnanoparticles may even stimulate growth and survival of seedlings or plant juvenile phases, exhibiting concurrently a sterilizing effect against pathogenic microorganisms from their environment to protect plants against diseases in their early stages of life [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…27 Leaf explants of Vitis vinifera 'Farkhi', 'Khoshnave' and 'Rashe' were successfully decontaminated with 95% EtOH for 30 s, and 1000 mg L À1 Ag NPs for 20 min. 28 Mahna et al 29 investigated the effect of Ag NP treatment on surface disinfection of Arabidopsis seeds, potato leaves and tomato cotyledons. The treatment of the explants with 100 mg L À1 Ag NPs for 1 or 5 min was found to be ideal for decontaminating (100%) the seeds, leaves or cotyledons and this treatment had no side effects on explant viability.…”
Section: Input Of Nanomaterials For Surface Disinfection Of Explantsmentioning
confidence: 99%
“…Ag NP has successfully controlled bacterial and fungal infection without any adverse effect on regeneration of lemongrass plantations (Fakhrfeshani et al, 2012). It has also been reported that NS can be an effective tool for eliminating contaminants from tissues only if the correct dose and exposure time are used (Mahna et al, 2013). However, NS has not yet become a universal decontaminant and our result will contribute to future research to find an effective way to control microbial contamination in the plant tissue culture.…”
Section: Resultsmentioning
confidence: 69%